A Case of Concurrent Miller-Dieker Syndrome (17p13.3 Deletion) and 22q11.2 Deletion Syndrome - Atwal, Paldeep S. (J Pediatr Genet, 2015)
Features of Miller-Dieker syndrome (MDS, 17p13.3 deletion syndrome, LIS1-associated lissencephaly) include classic lissencephaly, microcephaly, cardiac malformations, growth restriction, and characteristic facial changes. Individuals with 22q11.2 deletion syndrome (DiGeorge syndrome or velocardiofacial syndrome) are known to have congenital cardiac malformations (in particular conotruncal defects), palatal abnormalities (especially velopharyngeal insufficiency), hypocalcemia, immune deficiency, learning disabilities, and characteristic facial features. This case report describes phenotypic characteristics of a patient with extremely rare instance of having both MDS and 22q11.2 deletion syndrome that is unique in the medical literature. Prognosis in this concurrent phenotype is poor with our patient suffering from several malformations seen in both conditions and expiring in the neonatal period.